Construction and optimization of Fe3O4/C/ceramic composite absorbents by one-step recycling red mud and coal hydrogasification residue. (March 2023) - Liang, Liping; Du, Xiuning; Gao, Xuzhou; Wang, Yake; Zhang, Jinpeng; Xue, Xiaojie; Shi, Shuping; Su, Ningjing; Zhang, Kewei; Li, Guomin
Abstract: To realize the effective control of electromagnetic (EM) radiation and rational disposal of industrial wastes, Fe3 O4 /C/ceramic composites for microwave absorption were constructed through a solid phase synthesis process by synergistical recycling red mud (RM) and coal hydrogasification residue (CHR). The suitable synthesis temperature was 700 °C. And the performance of composites showed strong tolerance to the composition changes of RM-CHR mixture. The optimal performance was achieved on the composites with initial mass ratio of RM to CHR at 2:1 and 2.5:1. For a matching thickness of 1.5 mm, the effective absorption bandwidth ( EAB ) could reach 4.9 GHz with the lowest reflection loss of around − 20 dB. As the matching thickness ranges from 1.5 to 5.5 mm, the EAB values of two composites both cover about 90 % of the testing frequency range, 2 − 18 GHz. By virtue of the facile adjustment on both content of carbon and Fe3 O4 as well as graphitization degree, the tunable initial system composition play an important role in regulating the EM parameters to realize impedance matching. Meanwhile, the strong dielectric loss that stems from graphite carbon and abundant interfaces ensures the strong intrinsic attenuation ability of the composites. Graphical Abstract: ga1 Highlights: Solid wastes were recycled to construct materials to control microwave pollution. Fe3 O4 /C/ceramic composites possess satisfactory absorption performance. Impedance matching and dielectric loss play a key role to performance. Graphite carbon and numerous interfaces contribute to the dielectric loss.